The yeast molecular chaperone, Hsp104, influences transthyretin aggregate formation - Knier, Adam S.; Davis, Emily E.; Buchholz, Hannah E.; Dorweiler, Jane E.; Flannagan, Lauryn E.; Manogaran, Anita L. (Frontiers in Molecular Neuroscience, 2022)
Patients with the fatal disorder Transthyretin Amyloidosis (ATTR) experience polyneuropathy through the progressive destruction of peripheral nervous tissue. In these patients, the transthyretin (TTR) protein dissociates from its functional tetrameric structure, misfolds, and aggregates into extracellular amyloid deposits that are associated with disease progression. These aggregates form large fibrillar structures as well as shorter oligomeric aggregates that are suspected to be cytotoxic. Several studies have shown that these extracellular TTR aggregates enter the cell and accumulate intracellularly, which is associated with increased proteostasis response. However, there are limited experimental models to study how proteostasis influences internalized TTR aggregates. Here, we use a humanized yeast system to recapitulate intracellular TTR aggregating protein in vivo. The yeast molecular chaperone Hsp104 is a disaggregase that has been shown to fragment amyloidogenic aggregates associated with certain yeast prions and reduce protein aggregation associated with human neurogenerative diseases. In yeast, we found that TTR forms both SDS-resistant oligomers and SDS-sensitive large molecular weight complexes. In actively dividing cultures, Hsp104 has no impact on oligomeric or large aggregate populations, yet overexpression of Hsp104 is loosely associated with an increase in overall aggregate size. Interestingly, a potentiating mutation in the middle domain of Hsp104 consistently results in an increase in overall TTR aggregate size. These data suggest a novel approach to aggregate management, where the Hsp104 variant shifts aggregate populations away from toxic oligomeric species to more inert larger aggregates. In aged cultures Hsp104 overexpression has no impact on TTR aggregation profiles suggesting that these chaperone approaches to shift aggregate populations are not effective with age, possibly due to proteostasis decline.